Statistical analysis of teachers' digital competence levels - S. V. Avilkina (Статистика и экономика, 2020)
Purpose of the study. The study of the qualitative parameters of the human resources potential of the economy is necessary to describe the conditions in which digitalization processes develop, to identify the problems of training specialists. The professional education system is considered in the article as an institution that provides human resources to the digital economy of the region. Innovative processes increase the requirements not only for the system of training specialists, but also for the skills of the lecturer, individual level of mastering information and communication technologies. The purpose of this study is to diagnose the levels of digital competencies of lecturers of professional educational institutions and to identify, on the basis of statistical analysis, the impact on the level of digital competencies of a lecturer of various parameters, such as the lecturer’s age; the disciplines he/her teaches; the data of continuing education in the field of information and communication technologies.Materials and methods. This paper provides an overview of approaches to solving the problems of staffing education in the context of informatization. Taking into account the proposed model of digital competencies of lecturers, the testing complex was approved. Methods of statistical data analysis were applied: descriptive statistics, correlation coefficients were calculated, a range diagram and scatter diagrams of lecturers' testing results were constructed. For the information processing, the qualitative indicators were converted into quantitative ones and the statistical analysis software packages were used: Microsoft Excel and STATISTICA 10.0.Results. As a result of the lecturers’ testing of professional educational institutions and statistical analysis, data were obtained on the level of human resources in terms of the formation of knowledge and skills in the field of information and computer technologies. The relationship between the level of digital competence and various factors has been identified. The factors that were analyzed in the course of the study: age, subjects taught, the period of limitation of the advanced training in the field of information and communication technologies.Conclusion. The introduction of the proposed model of competencies and diagnostic methods will allow diagnosing lecturers' skills in working in a digital environment and will ensure the adoption of informed managerial decisions in the development of the human resources of the vocational education system both at the level of the educational organization and at the level of public administration bodies. This model can be used to obtain information about the formation of digital competencies of different groups: employees of organizations and enterprises, state and municipal employees.